Potential for consortial relations among special libraries in Singapore. - Chiang, Mei Ling. (2008)
This study seeks to examine the prospects for consortial arrangements to develop among libraries in Singapore, in particular, whether there is such interest among government and quasi-government libraries. The benefits of engaging in consortia are many, chief among which are cost savings, greater access to resources and a stronger bargaining position vis a vis information vendors. This study seeks to examine interest in consortial collaboration, particularly in the areas of acquiring access to electronic news information resources, the problems envisaged by librarians, the prospects and the opportunities for consortiums to develop.